The Corporate Image of Audit Firms on Service Quality Auditee Satisfaction on Sme Firms in Malaysia: A Conceptual Study - Ukaabuilu, Ashari Bin Ismail; Ukaabuilu, Mohammed Hariri Bin Bakri; Ukaabuilu, Mohd Norazmi Bin Nordin; Ukaabuilu, Ahmad Aizuddin Hamzah; Ukaabuilu, Salmalina Salleh; Ukaabuilu, Junaidah Yusof; Ukaabuilu, Asrizam Esam (International Journal of Educational Excellence and Innovation, 2024)
This article aims to understand the association between service quality and auditee satisfaction with mediating corporate image employed through the structural equation model. A structured survey questionnaire was prepared to collect data from participants of Malaysian S.M.E.s. A convenience sampling method was used to select potential participants in this study. The results were expected to show positive and significant effects of service quality constructs, auditee satisfaction and corporate image. The finding was also expected that audit firms would concentrate on the corporate image with the service quality and auditee satisfaction for improving their auditee’s satisfaction.